PJMHS 2022
DOI: 10.53350/pjmhs22166185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Effect of Closed Kinetic Chain and Open Kinetic Chain exercises in the strengthening of Vastus Medialis Obliqus in subjects with Patello-Femoral Pain Syndrome - a randomized control trial

Abstract: Aim: To compare the effects of closed kinetic chain and open kinetic chain exercises in the strengthening of vastus medialis obliqus in subjects with Patello-femoral pain syndrome. Methods: The study was a randomized controlled trial. It was conducted to compare the impact of open and closed kinetic chain exercises to strengthen the Vastus medialis obliqus in PFPS patients. For this purpose, 36 patients both males and females with age 20-40 years having PFPS were allocated randomly to two experimental (group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…CKC exercises facilitate the neuromuscular system, which in turn leads to better functioning of the joint. At the same time, they improve proprioception and increase joint stabilization 26,27 . Leite et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKC exercises facilitate the neuromuscular system, which in turn leads to better functioning of the joint. At the same time, they improve proprioception and increase joint stabilization 26,27 . Leite et al.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Leite et al investigated the acute effects of proprioceptive CKC exercises on proprioception. They applied aerobic training to one group and proprioceptive exercises to the other group and observed that the greatest reduction in angular error occurred in the group receiving proprioceptive CKC exercises 28.…”
mentioning
confidence: 99%